Profile Of Sedentary Lifestyle, Physical Activity And Obesity In Physical Education Students - Hadi, Santika Rentika; Ardian Fufu, Ronald Dwi; Fefrian Rosmi, Yandika; Mardhika, Riga; Utamayasa, I Gede Dharma (Jurnal Sains dan Teknologi, 2023)
Exercising is basically the need of every human being in his life, so that his physical condition and health are always well maintained. The purpose of conducting this research is to describe or profile the sedentary lifestyle of students at PGRI Adi Buana University, Surabaya, class of 2022. In this research, the survey method was carried out on students at PGRI Adi Buana Surabaya University, Department of Physical Education, Class of 2020. This type of research is a quantitative research approach. descriptive. The population and sample of this study were 50 people. This survey research used the International Physical Activity Questionnaire (IPAQ) questionnaire using the Google form, which then shared the link via WA. The results of the research above show that the description of the results of adolescents at the PGRI Adi Buana University Surabaya Department of Physical Education class of 2020 who spend sedentary time is in the low category with a percentage of 56% and spending high sedentary time is only 44%. Based on the results of a sedentary lifestyle profile study, there were physical education students at the University of PGRI Adi Buana Surabaya, it was found that they settled in the moderate category.